Pilot interference mitigation for TDD cell-free massive MIMO systems - Yue WANG; Fangmin XU; Haiyan CAO (Dianxin kexue)
To alleviate the pilot interference for cell-free massive multi-input multi-output (MIMO) system and improve system’s performance, a comprehensive approach including the pilot reuse, access point (AP) selection and power allocation was proposed.Firstly, to alleviate the pilot contamination, the pilot assignment based on the order of user distance was proposed, in which the pilot sharing was only allowed when the distance between two users is large enough to reduce the impact of pilot reuse.Then, by AP selection, only the APs which have main impact on the macro diversity gain were selected as the user’s serving APs.Finally, a modified max-min power control algorithm was proposed to improve the system’s average throughput.Simulation results show that the pilot interference mitigation strategy proposed improves the performance of the system significantly.